Pulsed breakdown mechanism of short vacuum gaps in nanosecond range; Pt. 2; Proceedings of the IIIrd International Symposium on Discharges and Electrical Insulation in Vacuum, Paris, 1968 - Bugaev S. P. (1968, 1968)
В фонде НТБ ТПУ отсутствует